Language in schizophrenia and aphasia: the relationship with non-verbal cognition and thought disorder. Issue 6 (2nd November 2019) - Little, Bethany; Gallagher, Peter; Zimmerer, Vitor; Varley, Rosemary; Douglas, Maggie; Spencer, Helen; Çokal, Derya; Deamer, Felicity; Turkington, Douglas; Ferrier, I. Nicol; Hinzen, Wolfram; Watson, Stuart
ABSTRACT: Objective: To determine the relationship between language abnormalities and broader cognitive impairment and thought disorder by examining language and cognition in schizophrenia and aphasia (a primary language disorder). Methods: Cognitive and linguistic profiles were measured with a battery of standardised tests, and compared in a clinical population of n = 50 ( n = 30 with schizophrenia and n = 20 with aphasia) and n = 61 non-clinical comparisons ( n = 45 healthy controls and n = 16 non-affected first-degree relatives of patients with schizophrenia). Results: Both clinical groups showed linguistic deficits. Verbal impairment was more severe in participants with aphasia, whereas non-verbal performance was more affected in participants with schizophrenia. In schizophrenia, but not in aphasia, verbal and non-verbal performance were associated. Formal thought disorder was associated with impairment in executive function and in grammatical, but not naming, tasks. Conclusion: While patients with schizophrenia and aphasia showed language impairments, the nature and cognitive basis of these impairments may be different; language performance disassociates from broader cognitive functioning in aphasia but may be an intrinsic expression of a broader cognitive impairment in schizophrenia. Thought disorder may represent a core malfunction of grammatical processing. Results suggests that communicative ability may be a valid target in cognitive remediation strategies in schizophrenia.